Strategi Public Relation Dalam Meningkatkan Citra Perusahaan Di Era New Normal Studi Kasus Suvana Jakarta Golf - Erlangga, Christopher Yudha (Jurnal Public Relations (J-PR), 2020)
This research is a research on how to use SWOT analysis in the Public Relations strategy of an organization. The formulation of the problem in this research is "How is the Public Relations Strategy in Improving the Image". The method used is SWOT analysis and using qualitative descriptive research methods. By providing a matrix for the discussion, it was found that an organization could first analyze the organization's internals and could find a description of the problem in increasing visitor interest.